Proficiencies in business diplomacy: A comprehensive literature review - Njiru, Jeniffer Karimi; Thanitbenjasith, Phithagorn; Nwafor, Lloyd Chukwuemeka (Edelweiss Applied Science and Technology, 2025)
Business diplomacy enables organizations to effectively influence international entities, navigate geopolitical and economic challenges, and engage in negotiations with diverse corporate and non-business stakeholders. Despite the emerging nature of business diplomacy and its significant implications for enterprises and international relations, there has been limited research focused on the business diplomacy competencies of tourism managers in Kenya. The research employed a meta-analysis of studies on business diplomacy competencies, conducted through an extensive literature review. The study sample comprised 26 research outcomes closely associated with business diplomacy and the tourism sector. The focus was on categorizing the research themes, identifying the locations of the studies, and examining the methodologies employed. The investigation yielded three primary findings. Previous studies were conducted outside of Africa and did not concentrate on tourism. The majority of studies employed desk research methodologies, including questionnaires, case studies, interpretive exploratory techniques, and literature reviews. The limited number of survey research studies accompanied by interview guides restricts managers’ ability to innovate in business diplomacy and hinders the acquisition of new empirical data necessary for enhancing the existing literature. The report concludes by identifying several areas that may necessitate further research to develop a competency model aimed at enhancing the business diplomacy competency of managers, particularly in the Kenyan tourism industry.